Does Lower Debt Buy Higher Growth? : The Impact of Debt Relief Initiatives on Growth - Marcelino, Sandra (IMF Working Papers; Working Paper ;, 2014)
In 1996, the IMF and the World Bank introduced the Heavily Indebted Poor Countries Initiative-a comprehensive debt relief program aimed at reducing the external debt burden of eligible countries to sustainable levels, provided they carry out strong programs of macroeconomic adjustment and structural reforms designed to promote growth and reduce poverty. Now that the HIPC Initiative is nearly completed, this paper investigates whether the initiative managed to spur growth, either directly or indirectly through investment. In contrast to earlier studies, we conclude that there is some evidence of positive effects of the HIPC Initiative on growth. Such evidence suggests that the HIPC Initiative and MDRI have helped HIPC-eligible countries to reach higher growth, but it remains unclear whether this is through higher investment or another channel. Also, the analysis illustrates that it is hard to disentangle pure debt-relief effects from other concurrent factors.